Trade-off or tension: Can carbon be priced without risking economic competitiveness? - Jakob Hafele; Sonia Kuhls (ZOE. Institut für zukunftsfähige Ökonomien, 2022)
While reducing industrial greenhouse gas (GHG) emissions is undoubtedly necessary to avoid an ecological disaster, political support for environmental regulation depends largely on its effectiveness and expected side-effects. A potential fallout often associated with environmental policies is a decline in economic competitiveness. Therefore, it is vital to understand whether there is a trade-off, implying that climate mitigation policies necessarily lead to competitiveness losses, or if a suitable policy design can achieve climate change mitigation without risking significant losses in competitiveness. This paper provides a systematic overview of the existing literature - including modelling studies and econometric analyses - regarding the association between GHG emissions reductions and competitiveness risks. To structure the literature, we develop a framework that allows us to cluster the reviewed papers by their theoretical and their empirical approach, rendering possible the analysis of differences between the resulting clusters. Scrutinising the findings of 80 papers, we determine that declines in competitiveness and industrial relocation to unregulated countries (carbon leakage) have so far not been relevant outcomes of existing environmental policies, neither on the firm nor on the country level. Nevertheless, they should not be neglected in the assessment of future policies, as modelling studies foresee small but significant levels of comparative disadvantages and carbon leakage. We discuss potential reasons for this discrepancy between study approaches. Overall, the empirical evidence suggests that carbon pricing regulation and economic competitiveness can be reconciled under specific circumstances, which must be provided by a coherent policy mix that takes climate change mitigation seriously while addressing possible negative side-effects.
Keywords: 330; Carbon Pricing; Comparative Advantage; Competitiveness; International Trade; Technological Innovation